(untitled) (Semiárida, 2020)
The essay was carried out to determine the effect of defoliation frequency on yields, dry matter composition and protein content in three Old World bluestems cultivars (Bothriochloa sp cv. Dahl, Spar, Plains) and one of sideoats grama (Bouteloua curtipendula (Mich.) Torrey cv. Vaughn) on the growth season. Defoliation (4 frequencies) and participants were arranged within a split plot design. Yields of whole plant dry matter (WPY) and blade (LY) -kg.ha-1.y-1, crude protein content In L (CP, %), yield of CP of L (CPY, kg.ha-1.y-1) and mean values of growth rate (gr, kgDM.ha-1.d-1) for WP and L were measured. Data were analyzed by proc GLM (SAS) and means were compared by Tukey test (p<0,05). Accumulated mean values: Dahl had the highest LY; between treatments, except Dahl, the lowest values Of LY,’ CP and CPY corresponded to T4 (single cut). Discriminated cutting values: in T l -T2 the WPY, LY and CPY of the 2 first cuttings were significative higher (even with exceptions), corresponding the upper cut rates to cutting 2. CP content was lowest in cutting 1, by senescence of L. It is concluded that cv. Dahl is the best of the forage species and cultivars under evaluation, due to its high LY when defoliated at frequencies of 28, 35 or 45 days. At these frequencies, the leaves harvested a CP concentration of at least 8%.